Multiphysics 3D modelling of ironless permanent magnet generators - Zhang, Z.; Muyeen, S.M.; Al-Durra, A.; Nilssen, R.; Nysveen, A. (2014)
Analytical method is widely used for the preliminary design and optimization of electrical machines. It has short calculation time and low computational cost (cost of simulation codes and supporting hardware), but the calculate result is normally considered to be not as accurate as finite element method (FEM). On the other hand, it is time-consuming to optimize machines with FEM if the optimization is not parallelized. Parallelizing optimization requires many licenses when commercial FEM codes are used, which can be very expensive. Ironless permanent magnet generator has large diameter and small aspect ratio, therefore, multiphysics approach is expected to be used for investigating the magnetic and thermal field. To address the above challenges, this paper presents a multiphysics modelling strategy for the design and optimization of ironless permanent magnet generators. Open-source codes are used to reduce the computational cost. A design example is presented to demonstrate the detail of this design method. This approach is expected to be used in super computer in the future, so that the calculation time can be largely reduced.